PENGARUH MOTIVASI TERHADAP KINERJA DAN PENGARUH KINERJA TERHADAP KEPUASAN KERJA GURU DIMODERASI BUDAYA ORGANISASIONAL (Studi Pada Guru PNS SMP Negeri Di Wilayah Kecamatan Ulujami Kabupaten Pemalang) - Tri Winarsih, 1352020035; ., Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study was to investigate the effect motivation on the teacher performance and the effect teacher performance on job satisfaction with organizational culture moderated. The specific objectives of the study was to examine and analyze the effect of motivation to work on teacher performance, the influence of teacher performance on job satisfaction of teachers, the influence of organizational culture on job satisfaction of teachers and the role of organizational culture in the influence of teacher performance on job satisfaction of teachers. This research is an explanatory research study that proves the effect motivation on the teacher performance and the effect teacher performance on job satisfaction with organizational culture moderated. This study uses the study population (census) amounted to 127 respondents. Data of this research is primary data obtained directly from the source. The method of data analysis using a model of moderation with a quasitype interaction techniques. The results showed that motivation positive effect on the performance of teachers SMP Negeri, in District Ulujami, Pemalang; performance of teachers positive effect on job satisfaction of teachers SMP Negeri, in District Ulujami, Pemalang;Â organizational culture has positive influence on job satisfaction of teachers in District Ulujami SMP Negeri, Pemalang and organizational culture weakens the influence of teachers performance on job satisfaction of teachers Ulujami SMP Negeri in the District Pemalang.Keywords: Motivation, Teacher Performance, Organizational Culture, Job Satisfaction